Sharia-Based Business Management Strategy in Islamic Civil Society Organization in Indonesia (Study at Al-Washliyah) - Burhanuddin Al-Butary; Azhari Akmal Tarigan; Fauzi Arif Lubis (Lembaga Bale Literasi, 2026)
Strengthening sharia-based business governance is a strategic need for Islamic civil society organizations to increase economic independence, institutional sustainability, and public service capacity amid the demands of organizational professionalization. Studies on sharia business management strategies in Islamic civil society organizations are still limited, especially in the context of Al-Washliyah which has a wide institutional network and the potential for business unit development. The purpose of this study is to analyze strategic orientation, resource governance, business unit development strategies, and strategic decision-making dynamics in sharia-based business management in Al-Washliyah. This study uses a qualitative approach with a case study design through the use of data from interviews, observations, documentation, and organizational archives, then analyzed thematically through data reduction, data presentation, and interpretation extraction. The results show that the strategic orientation of the business is directed towards the integration of sharia values, institutional vision, and the creation of socio-economic benefits, so that every business activity has organizational legitimacy and sustainable competitiveness. Resource governance shows the strengthening of leadership functions, accountability, coordination, and human resource capacity development that supports operational effectiveness. The strategy for the development of business units relies on the use of social capital, institutional networks, partnerships, and business diversification in accordance with the needs of the community. Strategic decision-making takes place in a participatory, adaptive, and balance-oriented manner between economic achievements, organizational sustainability, and socio-religious missions. These findings enrich the development of sharia business management theory and the study of Islamic civil society organizations as a reference to strengthen the business governance of Islamic organizations in Indonesia.